Primary Tumor Resection Plus Chemotherapy Versus Chemotherapy Alone for Colorectal Cancer Patients With Asymptomatic, Synchronous Unresectable Metastases (JCOG1007; iPACS): A Randomized Clinical Trial. Issue 10 (1st April 2021) - Kanemitsu, Yukihide; Shitara, Kohei; Mizusawa, Junki; Hamaguchi, Tetsuya; Shida, Dai; Komori, Koji; Ikeda, Satoshi; Ojima, Hitoshi; Ike, Hideyuki; Shiomi, Akio; Watanabe, Jun; Takii, Yasumasa; et al.
Abstract : PURPOSE: It remains controversial whether primary tumor resection (PTR) before chemotherapy improves survival in patients with colorectal cancer (CRC) with asymptomatic primary tumor and synchronous unresectable metastases. PATIENTS AND METHODS: This randomized phase III study investigated the superiority of PTR followed by chemotherapy versus chemotherapy alone in relation to overall survival (OS) in patients with unresectable stage IV asymptomatic CRC and three or fewer unresectable metastatic diseases confined to the liver, lungs, distant lymph nodes, or peritoneum. Chemotherapy regimens of either mFOLFOX6 plus bevacizumab or CapeOX plus bevacizumab were decided before study entry. The primary end point was OS, which was analyzed by intention-to-treat. RESULTS: Between June 2012 and September 2019, a total of 165 patients were randomly assigned to either chemotherapy alone (84 patients) or PTR plus chemotherapy (81 patients). When the first interim analysis was performed in September 2019 with 50% (114/227) of the expected events observed among 160 patients at the data cutoff date of June 5, 2019, the Data and Safety Monitoring Committee recommended early termination of the trial because of futility. With a median follow-up of 22.0 months, median OS was 25.9 months (95% CI, 19.9 to 31.5) in the PTR plus chemotherapy arm and 26.7 (95% CI, 21.9 to 32.5) in the chemotherapy-alone arm (hazard ratio, 1.10; 95% CI, 0.76 to 1.59; one-sided P = .69). Three postoperative deaths occurred in the PTR plus chemotherapy arm. CONCLUSION: Given that PTR followed by chemotherapy showed no survival benefit over chemotherapy alone, PTR should no longer be considered a standard of care for patients with CRC with asymptomatic primary tumors and synchronous unresectable metastases.